2006
DOI: 10.2355/isijinternational.46.1306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu, Sn and W on the Rate of Nitrogen Dissociation on the Surface of Molten Iron

Abstract: The effects of Cu, Sn and W on the rate of nitrogen dissociation on the surface of molten iron have been investigated at 1 973 K by an isotope exchange method. The rate constant of nitrogen dissociation increases with increasing the content of W. On the other hand, the rate constant decreases with increasing the Cu and Sn contents. These effects of the alloying elements on the rate of nitrogen dissociation depend on the affinity of the solute element with nitrogen in molten iron. The elements which have strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Figure 4), Ti, V, Nb, Cr, or Mn has similar effect on nitrogen activity coefficient and the coefficient rises with increasing the content of B, C, P, Si, S, Ni, or Cu. Those findings correspond well with previously reported ones [17][18][19][20] except for the effect of Al. It must be stressed that O and S are surface-active elements and even if S increases the activity coefficient of nitrogen and thus enhancing its removal rate, the total effect is negative.…”
Section: Boundary Treatmentsupporting
confidence: 94%
See 1 more Smart Citation
“…Figure 4), Ti, V, Nb, Cr, or Mn has similar effect on nitrogen activity coefficient and the coefficient rises with increasing the content of B, C, P, Si, S, Ni, or Cu. Those findings correspond well with previously reported ones [17][18][19][20] except for the effect of Al. It must be stressed that O and S are surface-active elements and even if S increases the activity coefficient of nitrogen and thus enhancing its removal rate, the total effect is negative.…”
Section: Boundary Treatmentsupporting
confidence: 94%
“…[14] Some related experiments on a laboratory scale have been conducted using a constant amount of surfaceactive elements and the results showed that the denitrogenation can be described as a second-order reaction. [8,15,16] The effect of some alloying elements on nitrogen removal behavior has also been examined [17][18][19][20][22][23][24] and the results revealed that the elements such as titanium (Ti), zirconium (Zr), vanadium (V), manganese (Mn), and chromium (Cr), which have stronger affinity with nitrogen than iron, would enhance the nitrogen dissociation rate (the reaction rate for the reverse reaction of nitrogen desorption), whereas the elements such as aluminum (Al), silicon (Si), boron (B), (copper) Cu, wolfram (W), and tin (Sn) having stronger repulsive force against nitrogen would retard the dissociation rate.…”
Section: Introductionmentioning
confidence: 99%
“…The work by Choh et al revealed that manganese (Mn) and copper (Cu) in liquid steel may reduce the interfacial temperature because of the latent heat of vaporization, thus decreasing the nitrogen removal rate. Morita et al and Ono‐Nakazato et al argued that the elements (i.e. Ti, Zr, V, Mn, and Cr) that have stronger affinity with nitrogen than iron, would enhance the nitrogen dissociation rate (the reaction rate for the reverse reaction of nitrogen desorption), while those elements (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, mass transfer resistance in gas and liquid phases has been discussed in the light of rate-controlling step and chemical reaction rate constant is also being clarified. [1][2][3][4][5][6][7] Moreover, effects of surface active elements such as sulfur and oxygen on chemical reaction rate constant have been recently studied by many researchers. [8][9][10] Many studies have also been reported on measurement method of nitrogen removal.…”
Section: Introductionmentioning
confidence: 99%